Real-life data on the comorbidities in spondyloarthritis from our multicenter nationwide registry: BioStar - H. Fatih Çay,; Meltem Alkan Melikoğlu,; Fatma Gül Yurdakul,; Hatice Bodur,; Şebnem Ataman,; Erhan Çapkın,; Gülcan Gürer,; İlhan Sezer,; M. Tuncay Duruöz,; Aylin Rezvani,; İlker Yağcı,; Feride Göğüş,; et al. (Archives of Rheumatology, 2023)
Objectives: Considering that the comorbid situations during the management of Spondyloarthritis (SpA) have been underlined in several recommendations, the main objective of this study was to evaluate the comorbid conditions of Turkish patients with SpA. Patients and methods: This cross-sectional observational study was conducted with 1,242 SpA patients (844 males, 398 females; mean age: 43.9±11.0 years; range, 19 to 81 years) diagnosed according to the modified New York criteria for ankylosing spondylitis or the Assessment of SpondyloArthritis International Society (ASAS) criteria. The patient data were collected from the Biologic and targeted Synthetic antirheumatic drugs Registry (BioStar) between February 1, 2019, and December 29, 2020. Clinical and demographic data, including, age, sex, disease duration, body mass index (BMI), pain, patient’s global assessment, physician’s global assessment, Bath Ankylosing Spondylitis Disease Activity Index, Ankylosing Spondylitis Disease Activity Score, Bath Ankylosing Spondylitis Functional Index, Bath Ankylosing Spondylitis Metrology Index, and Maastricht Enthesitis Score, were recorded. Comorbid conditions were recorded by filling out a questionnaire according to the clinical history or medical records. Charlson Comorbidity Index and Rheumatic Disease Comorbidity Index scores were calculated from the gathered comorbidity information. Results: Nine hundred thirteen patients had radiographic axial SpA, 153 had nonradiographic axial SpA, and 176 had peripheral SpA. The most common comorbidities were hypertension (HT) (n=167, 13.4%), diabetes mellitus (DM) (n=83, 6.7%), thyroid disorders (n=64, 5.6%), and depression (n=61, 4.9%). The comorbidities and the calculated comorbidity indices were significantly higher in females, in those with a BMI >25 kg/m2 , and those over 60 years of age. No relationship was found between smoking and alcohol use and comorbidities. A significantly higher prevalence of HT and DM in peripheral SpA patients and a lower prevalence of thyroid disorders in radiographic axial SpA patients were observed. Conclusion: The most commonly reported comorbidities were HT, DM, thyroid disorders, and depression in SpA patients according to the BioStar database. The frequency of comorbidities and composite comorbidity scores were higher among females, older (>60 years) patients, and overweight (BMI >25 kg/m2 ) patients.